Penegakan Hukum Terhadap Perdagangan Satwa Liar Menurut Undang-Undang Nomor 5 tahun 1990 - Bobi Darmawan; Olivia Anggie Johar (Universitas Lancang Kuning, 2021)
The issue in this topic is how the Pekanbaru City law enforces the wildlife trade, which is based on Law Number 5 of 1990 concerning the Conservation of Biological Natural Resources and Their Ecosystems. What are the challenges of law enforcement against wildlife trade in Pekanbaru City as outlined in Law Number 5 of 1990 concerning Conservation of Biological Natural Resources and Their Ecosystems? This research is a sociological legal research that uses data collection tools in the form of interviews. The conclusion of this article is that law enforcement against wildlife trade in Pekanbaru City has not been carried out optimally because there is still illegal wildlife trade in the jurisdiction of Pekanbaru. The existence of illegal wildlife trade activities proves this. Stumbling blocks for law enforcement Regulations that are no longer up to date are the cause of the prohibition of wildlife trade. Therefore, the legal umbrella number 5 of 1990 concerning the Conservation of Biological Natural Resources and their Ecosystems must be updated immediately, because they are no longer relevant to the times, and the existing sanctions can be seen. As not giving a sense of justice to resources, ecosystems and nature Uniform perception among law enforcement officers is also important to obtain a judicial process that provides a sense of justice. Improvements and additions to these facilities and infrastructure include educated and skilled human resources, adequate equipment, and adequate finances, including facilities and infrastructure to support and streamline the activities of law enforcement officers in preventing or carrying out repressive activities in the context of saving nature. its resources and ecosystem Increase legal awareness through legal counseling on protected animal species and sanctions for wildlife trade. Abstrak Isu dalam topik ini adalah bagaimana penegakan hukum Kota Pekanbaru terhadap perdagangan satwa liar, yang didasarkan pada Undang-Undang Nomor 5 Tahun 1990 Tentang Konservasi Sumber Daya Alam Hayati dan Ekosistemnya. Apa saja tantangan penegakan hukum terhadap perdagangan satwa liar di Kota Pekanbaru yang dituangkan dalam Undang-Undang Nomor 5 Tahun 1990 Tentang Konservasi Sumber Daya Alam Hayati dan Ekosistemnya? Penelitian ini merupakan penelitian hukum sosiologis yang menggunakan alat pengumpulan data berupa wawancara. Kesimpulan dari artikel ini adalah penegakan hukum terhadap perdagangan satwa liar di Pekanbaru Kota belum terlaksana secara optimal karena masih terdapat perdagangan satwa liar ilegal di wilayah hukum Pekanbaru. Adanya aktivitas perdagangan satwa liar ilegal membuktikan hal tersebut. Batu sandungan penegakan hukum Peraturan yang tidak lagi up to date menjadi penyebab pelarangan perdagangan satwa liar. Oleh karena itu, payung hukum nomor 5 tahun 1990 tentang Konservasi Sumber Daya Alam Hayati dan Ekosistemnya harus segera dimutakhirkan, karena sudah tidak relevan lagi dengan perkembangan zaman, dan terlihat sanksi yang ada. Sebagai tidak memberikan rasa keadilan terhadap sumber daya, Ekosistem dan alam Persepsi yang seragam di antara aparat penegak hukum juga penting untuk mendapatkan proses peradilan yang memberikan rasa keadilan. Perbaikan dan penambahan sarana dan prasarana tersebut meliputi sumber daya manusia yang terdidik dan terampil, peralatan yang memadai, dan keuangan yang memadai, antara lain sarana dan prasarana untuk mendukung dan mengefektifkan kegiatan aparat penegak hukum dalam mencegah atau melakukan kegiatan represif dalam rangka penyelamatan alam. sumber daya dan ekosistemnya Meningkatkan kesadaran hukum melalui penyuluhan hukum jenis satwa yang dilindungi dan sanksi perdagangan satwa liar.